(untitled) (Journal of the College of Basic Education, 2023)
Countables have two numbers in English : singular and plural ; and three numbers in Arabic: singular , dual and plural. The singular is the form to which suffixes are added to form the dual and the plural .These suffixes denote duality and plurality in reference .However , there are nouns which do not follow this rule . These are singular nouns that have plural reference such as team, family, army in English and قوم ,رهط ,جيش in Arabic . Such nouns are called collective nouns in English and أسماء الجموع in Arabic . The collective noun refers to a collection of living beings or lifeless things. The research in hand deals only with collective nouns of human multitude or simply human collective nouns as they are called throughout the research . Human beings all over the world need to be gathered in groups in different aspects of life , in different circumstances , and for different purposes . This leads to certain similarities when referring to these gatherings, however , there are factors such as culture , religion , and geography that may result in diversities . The study in hand aims at finding the similarities and differences between English and Arabic in expressing the idea of collectivity, classifying and deriving nouns to name human groups . The glorious Qur’anic verses have been a great aid for the study in illustrating and clarifying certain characteristics of human collectives especially when Arabic grammar books do not discuss or illustrate certain features of these nouns owing to the fact that Arabic do not talk about اسماء الجموع as a distinct subject but rather under the plural .